1976
DOI: 10.1136/gut.17.6.444
|View full text |Cite
|
Sign up to set email alerts
|

Electrogenic glucose absorption in untreated and treated coeliac disease.

Abstract: SUMMARY Using a method for measuring changes in transmural potential difference across the human jejunum in vivo, the operational kinetic parameters of 'Apparent Km' and PD max for the active electrogenic component of glucose absorption were estimated in a group of healthy volunteers and in patients with coeliac disease. Both the 'Apparent Km' (17 2 mM; mean SEM) and the PD max (8.6 ± 0 7 mV) in nine patients with untreated coeliac disease were significantly lower (p < 0 005) than in the control group ('Appare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
8
1

Year Published

1977
1977
1984
1984

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 20 publications
5
8
1
Order By: Relevance
“…Read et al [18] reported the values for Kt in normal adults of 36 + 6 mM in rive, while Sacher et al [19] reported a value of 5.5 mM in adults in vivo. On the other hand, the values of APDG max in the present study were almost identical to those reported by others [15][16][17][18][19]23]. The difference in the values of Kt seems not to be due to the difference in the true affinity of sugars at the transport site but to the difference of infusion method and/or the difference in the unstirred layer in the intestinal lumen.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Read et al [18] reported the values for Kt in normal adults of 36 + 6 mM in rive, while Sacher et al [19] reported a value of 5.5 mM in adults in vivo. On the other hand, the values of APDG max in the present study were almost identical to those reported by others [15][16][17][18][19]23]. The difference in the values of Kt seems not to be due to the difference in the true affinity of sugars at the transport site but to the difference of infusion method and/or the difference in the unstirred layer in the intestinal lumen.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to these in vitro experiments, changes in the transmural potential difference in vivo in both animal and human jejunum have been reported in association with intake or infusion of sugars [5,6,[15][16][17][18][19]23].…”
Section: Introductionmentioning
confidence: 99%
“…The PDmax in the active coeliac group (6f8 + 0 7 mV) was lower than in controls (7-6 + 0-6 mV) but not significantly so, while the PDmax in the treated coeliac group (10-6 + 0 9 mV) was significantly higher than in both the active coeliac and control groups. It should be noted that both operational kinetic parameters obtained in the present study are much lower than those obtained previously (Read et al, 1976b) because of the use of siphonage. Analysis of the results using a computer simulation indicates that the reduction in Apparent Km in active coeliac disease can be caused by the interaction of the decreased maximal absorption rate for glucose (Jmax) with the attenuated unstirred layer.…”
contrasting
confidence: 82%
“…Thus, pooling of successive solutions in the jejunum was minimised, allowing rapid change from one solution to the next; (2) intraluminal pressure was measured at the infusion site by means of a transducer (Bell and Howell, model 4-327 L221) connected to the side arm of the infusion column. This allowed us to check that intestinal motility, suppressed by propantheline bromide (Read et al, 1974(Read et al, , 1976bBrown et al, 1976), remained quiescent during the recording period; (3) both the pressure and the PD signals passed through electronic filters with fivesecond time constants to suppress fluctuations in the record caused by the infusion pump, respiration, electrocardiogram, intestinal myoelectric activity, and 50 Hz mains interference.…”
Section: Techniquesmentioning
confidence: 99%
See 1 more Smart Citation